Parsing Data Log Hasil Pemblokiran Situs Negatif Di Satuan Kerja Perangkat Aceh - Salsabilah, Adellia Divanda Riga; Zulfa, Ira; Saputra, Mahmuda (Jurnal Teknik Informatika dan Elektro, 2024)
In today's digital age, internet access has become an integral part of everyday life, providing broad access to information and communication. However, these technological advances also bring negative impacts, including the potential for the spread of unwanted content or harm to society. The process of parsing negative site blocking datalog is a technique used to analyze and decipher log data resulting from site blocking activities. In this context, negative site blocking is not only focused on illegal content, but also involves efforts to mitigate cybersecurity threats, including phishing attacks, malware, and other malicious online activities. Use of Observation Methods (Observation), Interviews, Literature Studies where the author made direct observations at the Aceh Communication, Informatics and Coding Agency to find out about the negative site blocking datalog in the Aceh Equipment Work Unit, conducted direct interviews with Field Supervisors and staff at the agency to find out about the process of parsing negative site blocking datalogs at the Aceh Equipment Work Unit, collect and study references related to data parsing, negative site categories, websites, CodeIgniter 4 documentation, Bootstrap documentation, and information system design tools from various journals, theses, articles, and various other reference sources. The proposed system for parsing datalogs has clear functional and non-functional needs. Functional needs involve features such as login, blocking data management, category management, blocking graph representation and reporting. Meanwhile, non-functional needs include authentication security, responsive performance, and an intuitive user interface. Thus, parsing log data resulting from negative site blocking in the Aceh Device Work Unit is expected to provide significant benefits for Diskominsa Aceh in maintaining cyber security and morality in the use of the internet in its territory. These conclusions highlight the importance of implementing sophisticated technology solutions to understand, analyze, and manage block log data efficiently and effectively.